Analysis of Growth and Changes in Economic Structure in 5 Big Cities on the Island of Sumatra (Case Study 2017-2022) - Nabilla, Nina; Ciptawaty, Ukhti; Ratih Y. T., Arivina; Yuliawan, Dedy; Murwiati, Asih (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to analyze the growth and changes in economic structure in five large cities on the island of Sumatra. This type of research is quantitative research. This research uses secondary data sourced from data from the Central Statistics Agency. The data used in this research is time series data from 2017-2022. The methods used in this research are the Structural Transformation analysis method, Location Quotient (LQ) analysis and Klassen Typology Analysis. The results of the research show that the economy in 5 large cities on the island of Sumatra experienced a negative shift in the primary economic sector, while most of the secondary and tertiary economic sectors experienced a positive shift or increased. The results of the Location Quotient (LQ) analysis have a significant effect on the Klassen Typology analysis, where the economic sector Non-based sectors in each region are in quadrant III, that is, these sectors are classified as non-based sectors but have the potential to be developed in the future, while non-based sectors in quadrant IV are categorized as economic sectors that are relatively underdeveloped and do not have a competitive advantage in the analysis area.